PENERAPAN TERAPI LUKA TEKANAN NEGATIF TERHADAP PENURUNAN TINGKAT INFEKSI LUKA OPERASI.: Application Of Negative Pressure Wound Therapy To Reduce The Rate Of Surgical Wound Infection - Fakrul Ardiansyah; Ade Ewa; Raju Kapadia; H. Amandus H. Amandus; Azhari Baedlawi; Vitria Wuri Handayani; Halina Rahayu; Puspa Whardani (Jurusan Keperawatan, 2024)
Negative pressure wound therapy has prevented postoperative wound complications, the surgical wound infection in high-risk patients such as postoperative gastrointestinal patients. Purpose This study aims to identify the results of nursing care and the negative pressure wound therapy on the level of infection in Mrs. J with septic shock in Dr. Abdul Aziz Singkawang. The method used by the author is a case study of nursing care starting from assessment, nursing diagnosis, nursing intervention, implementation, and evaluation of nursing and negative pressure wound therapy from May 9, 2022, to May 11, 2022. The results show that this study's nursing problems are spontaneous ventilation disorders, aspiration risk, gastrointestinal motility dysfunction, hypervolemia, and impaired skin/tissue integrity. After 3 days of implementation, it showed that the nursing problem didn't resolve and the negative pressure wound therapy could reduce the rate of surgical wound infection. The negative pressure wound therapy found a decrease in the rate of surgical wound infection, a decrease in the amount of exudate (14 ml to 9 ml), and a burning sensation (39.2°C to 37.9°C). Negative pressure wound therapy can reduce exudate, stabilizes the skin temperature around the wound, and reduces the number of bacteria, which is the wound healing process. Our suggestion is that negative pressure wound therapy can be applied with more samples and a longer time.